2022
DOI: 10.3390/biology11030405
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Evidence of Root-to-Shoot Signaling for the Coding of Support Thickness in Pea Plants

Abstract: Plants such as climbers characterized by stems or tendrils need to find a potential support (e.g., pole, stick, other plants or trees) to reach greater light exposure. Since the time when Darwin carried out research on climbing plants, several studies on plants’ searching and attachment behaviors have demonstrated their unique ability to process some features of a support to modulate their movements accordingly. Nevertheless, the strategies underlying this ability have yet to be uncovered. The present research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 52 publications
(102 reference statements)
0
15
0
Order By: Relevance
“…In this connection, previous evidence provides a degree of support that some climbing plants can modify their circumnutation patterns to a greater or lesser extent depending on the presence/absence of a potential support in the environment [24,25]. Experimental evidence demonstrating that this is the case has been forthcoming from recent studies that used kinematic analysis to characterize the movements of the tendrils of pea plants [6,[26][27][28]. Guerra and colleagues [29], for example, demonstrated that pea plants (Pisum sativum L.) are able to perceive a stimulus and modulate the kinematics of the tendrils according to the features of a potential support.…”
Section: Discussionmentioning
confidence: 98%
“…In this connection, previous evidence provides a degree of support that some climbing plants can modify their circumnutation patterns to a greater or lesser extent depending on the presence/absence of a potential support in the environment [24,25]. Experimental evidence demonstrating that this is the case has been forthcoming from recent studies that used kinematic analysis to characterize the movements of the tendrils of pea plants [6,[26][27][28]. Guerra and colleagues [29], for example, demonstrated that pea plants (Pisum sativum L.) are able to perceive a stimulus and modulate the kinematics of the tendrils according to the features of a potential support.…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, previous evidence provides a degree of support that some climbing plants can modify their circumnutation patterns to a greater or lesser extent depending on the presence/absence of a potential support in the environment [ 24 , 25 ]. Experimental evidence demonstrating that this is the case has been forthcoming from recent studies that used kinematic analysis to characterize the movements of the tendrils of pea plants [ 6 , 26 , 27 , 28 ]. Guerra and colleagues [ 29 ], for example, demonstrated that pea plants ( Pisum sativum L.) are able to perceive a stimulus and modulate the kinematics of the tendrils according to the features of a potential support.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on climbing plant behavior have elucidated mechanistic details of support searching and attachment [e.g., 3]. This body of research relies chiefly on field observations reporting on morphological or physiological responses [ 4 ], as well as on laboratory studies focused on the characterization of kinematical patterning through the use of time-lapse photography [ 5 , 6 ]. Although this body of research provides some quantitative data, the process is admittedly subjective and rather preliminary.…”
Section: Introductionmentioning
confidence: 99%
“…A point worth noting is that most studies on how climbers select a support based on diameter information focus on the final coiling response, with no or little reference to the choreography assumed by the tendrils during the approach phase [7,8,22]. To fill this gap, we have measured the kinematics of tendrils' circumnutation from the start of their growth until they grasped the support.…”
Section: Discussionmentioning
confidence: 99%
“…circumnutation patterns to a greater or lesser extent depending on features of potential supports with respect to what would be expected by chance movement. Experimental evidence demonstrating that this might indeed be the case has been forthcoming from recent studies that used kinematic analysis to characterize the movements of the tendrils of pea plants (Pisum sativum L.) [5][6][7][8][9]. Guerra and colleagues demonstrated that pea plants are able to perceive a support and modulate the kinematics of the tendrils' aperture depending on its thickness [7].…”
Section: Introductionmentioning
confidence: 99%